When bullying crosses the screen - Seixas, Sónia Raquel Pereira Malta Marruaz (2021)
Bullying is one of the most difficult areas of violence against children to eliminate, especially with the ubiquitous role that internet and mobile technology plays in their life today and the capacity this gives for bullying to continue night and day. Bullying seems to be part of human nature and has been with us since ancient times, but that is no reason to accept it fatalistically as “natural“ and, for children, part of growing up. Only in the 1970s was research first undertaken to explore the phenomenon and to attempt to understand why it takes place and its impact on individuals and societies. With the emergence of the internet and social media, bullying has taken a more sinister turn, becoming more relentless, constant and inescapable for victims. This book aims to explain to both experts and the interested layperson what is known about bullying, its causes, effects and, crucially, how it can be reduced, in particular by fostering social and emotional skills in young people. Authors from more than a dozen countries have contributed to this publication, presenting widely differing perspectives, practice and insights on how they are tackling or think we should be tackling modern societal issues such as bullying and hate speech. While some chapters focus more specifically on case studies and what the research tells us, others look at issues related to bringing up and educating children for the world we live in. This publication also provides information on the work of the ENABLE network and aims to introduce readers to the psychologists and researchers, teachers, parents and social media innovators that have helped to shape it.